Financování projektů ze zdrojů EU - Medová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2013)
Předmětem diplomové práce Financování projektů z fondů EU je charakteristika problematiky získávání finančních prostředků pro projekty z fondů EU. Teoretická část obsahuje poznatky z oblasti projektového managementu a strukturálních fondů EU. Praktická část práce zahrnuje vypracování studie proveditelnosti projektu spolufinancovaného z evropských fondů. V závěru práce je zpracován postup podání žádosti.

The topic of the diploma thesis Project Financing from EU Funds is the characteristics of the issue of raising funds for projects funded prom the EU. Theoretical part contains knowledge about project management and structural funds. The practical part includes prepare a feasibility study of the project. This project will be co-financed from EU Funds. In the end of the thesis is processed the whole procedure of submission the request.
Project Funding from EU financial resources
Keywords: Projekt; projektový management; studie proveditelnosti; evropské fondy; operační programy; analýza.; Project; Project Management; Feasibility Study; European Funds; Operational Programs; analysis.